An overview and comparison of the Versatile Video Coding standard - Pydych, Tomáš; Svoboda, Jaroslav; Krauz, Tomáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
This thesis mainly focuses on the Versatile Video Coding standard. It goes over the history of relevant video coding technologies of the same nature, giving a brief rundown of significant details of each piece of technology, with illustrations throughout. It tells about the development of Versatile Video Coding and relevant context, ending that section with a report about industry adoption of this technology and some future projections. It goes into detail about specific improvements upon preceding technology, alongside all relevant context thereof. In the methods section, it describes ways in which metrics of the quality of video footage can be objectively measured, calculated and compared. The next section presents the reader with results of objective video testing performed. Measured data suggests that the VVC codec is generally superior to prior video coding technology in quality. Available data seems to hint at VVC seeing wider adoption in future, despite competition. A window into performance aspects of this technology, that this thesis gives, should inform the author of those aspects as well, and help them choose between some of the presets VVC works on.
Vedoucí práce: Jaroslav Svoboda
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses